Sustainable isomaltulose production in Corynebacterium glutamicum by engineering the thermostability of sucrose isomerase coupled with one-step simplified cell immobilization - Hu, Mengkai; Liu, Fei; Wang, Zhi; Shao, Minglong; Xu, Meijuan; Yang, Taowei; Zhang, Rongzhen; Zhang, Xian; Rao, Zhiming (Frontiers in Microbiology, 2022)
Sucrose isomerase (SI), catalyzing sucrose to isomaltulose, has been widely used in isomaltulose production, but its poor thermostability is still resisted in sustainable batches production. Here, protein engineering and one-step immobilized cell strategy were simultaneously coupled to maintain steady state for long-term operational stabilities. First, rational design of Pantoea dispersa SI (PdSI) for improving its thermostability by predicting and substituting the unstable amino acid residues was investigated using computational analysis. After screening mutagenesis library, two single mutants (PdSIV280L, PdSIS499F) displayed favorable characteristics on thermostability, and further study found that the double mutant PdSIV280L/S499F could stabilize PdSIWT better. Compared with PdSIWT, PdSIV280L/S499F displayed a 3.2°C-higher Tm, and showed a 9-fold prolonged half-life at 45℃. Subsequently, a one-step simplified immobilization method was developed for encapsulation of PdSIV280L/S499F in food-grade Corynebacterium glutamicum cells to further enhance the recyclability of isomaltulose production. Recombinant cells expressing combinatorial mutant (RCSI2) were successfully immobilized in 2.5% sodium alginate without prior permeabilization. The immobilized RCSI2 showed that the maximum yield of isomaltulose by batch conversion reached to 453.0 g/L isomaltulose with a productivity of 41.2 g/l/h from 500.0 g/L sucrose solution, and the conversion rate remained 83.2 % after 26 repeated batches.